Organizational innovation as a factor of business competitiveness in Mypes during Covid-19. - García Monsalve, Jhenyfer Jhoana; Tumbajulca Ramírez, Isban Adilson; Cruz Tarrillo, José Joel (Escuela Profesional de Ciencias de la Comunicación Social de la Universidad Nacional del Altiplano, 2021)
This research aims to determine the influence of organizational innovation on business competitiveness in times of Covid-19 in the mypes of the commerce sector. It is of a basic type with a correlational descriptive scope. The research design is non-experimental, cross-sectional. The study participants are 200 managers. The instruments used were validated by expert judgment and their reliability was verified through Cronbach’s Alpha with a coefficient of 0.886 for organizational innovation and 0.778 for business competitiveness. The results show that there is a significant relationship between Business Innovation and Competitiveness (r = 0.459) with a significance of (p-value = 0.000), therefore, it can be affirmed that those mypes that bet on an innovation in the form to offer and / or provide their service or product will be able to remain in the market despite the crisis, this can be confirmed with the results that show us that 81% of companies that innovate are more competitive than the 19% that do not made.